Comics art - Gravett, Paul (New Haven : Yale University Press, 2013)
In this fascinating survey, acclaimed author Paul Gravett considers the vast output of comics culture from the late 19th century to today, tracing international lines of influence and examining major themes in contemporary comics.
Encompassing comics : the other history -- Frames of reference : properties of comics -- More than words can say : silent comics -- Between the panels : the power of the panel -- Unheard voices : who is afraid of comics? -- First-persons singular : autobiography in comics -- The human touch : style and individuality -- Infinite canvases : comics in the digital age.
boek
Keywords: Comic books, strips, etc. -- History and criticism; Comic books, strips, etc. -- Influence on mass media; Graphic novels -- History and criticism; Intermediality